ANALISIS KEPARAHAN INTERAKSI OBAT-OBAT POTENSIAL DI APOTEK DAERAH PESISIR PANTAI SURABAYA - Ana Khusnul Faizah; Hardyono Hardyono; Yuli Ainun Najih (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2021)
Potential drug-drug interactions (pDDIs) is one the drug related problems when two or more drugs given at the same time. DDIs are often predictable and avoidable. One of pharmacist roles is to assess prescription includes indication, dose, duplication therapy, adverse drug reaction, contraindication and DDIs, to identify, prevent and resolve DRPs. The objective of this study is to evaluate potential drug-drug interactions (pDDIs) in patients in east coast pharmacy in Surabaya. This study was performed by cross sectional of retrospective prescription in east coast pharmacy in Surabaya during March until May 2016. There were 780 prescriptions. Prevalence of pDDIs were 20,5%.Moderate pDDIs dominated 70% followed by minor (21%), major (8%) and contraindication (1%). The mechanisms of pDDIs is 82% by pharmacokinetic and 12% by pharmacodynamic. A Pharmacist should participate to identify and prevent harmful DDIs.